Characterization of fluorescent pseudomonads and their evaluation against Ralstonia solanacearum(Smith) Yabuuchi under Meghalaya condition - Kipgen, T.Lhingkhanthem; Majumder, Dipali (Umiam : CPGS, CAU, 2010)
Utilization of rhizospheric microbiota to induce plant growth and control of plant diseases is one of the important approaches to reduce environmental impact of hazardous chemicals. Fluorescent Pseudomonads are often predominant among plant rhizosphere associated bacteria. The rhizospheric fluorescent Pseudomonads of Meghalaya region have not yet been characterized and documented. The present investigation was focused on characterization of fluorescent Pseudomonads and their evaluation against Ralstonia solanacearum (Smith) Yabuuchi under Meghalaya condition. Soil samples were collected from rhizospheric regions of rice and maize crop from three districts viz., Ri-bhoi, East Khasi Hills and West Garo Hills districts of Meghalaya and 30 fluorescent Pseudo monads were isolated. On the basis of biochemical and cultural properties, 21 fluorescent Pseudomonads were identified as Pseudomonas jluorescens and tentatively designated as biovar I, II, III and V with 12, 7, 1 and 1 number of isolates respectively, whereas 3 isolates were identified as P. putida. The largest numbers of isolates were grouped in biovar I and most of these isolates were collected from rice rhizosphere. Hierarchical cluster analysis using Bray Curtis resemblance matrix on the basis of 16 biochemical tests of 21 Pseudomonas jluorescens, generated 3 distinct clusters at 96 per cent similarity level. Molecular characterization of 30 fluorescent Pseudomonads based on BOX Polymerase Chain Reaction (PCR) generated 12 amplification profile and the most prevalent profile was 'L' (9 isolates) with a band size of 750 bp, associated only with isolates of rice rhizosphere. Seven fluorescent Pseudo monads were screened on the basis of their HCN production and amplification by using pyrrolnitrin (PRNPrncf 5'CCACCAAGCCCGGCCAGGAGC-3' PRNPrncr 5'-GAGAAGAGCGGGTC GATGAAGCC-3') primer and tested for in vitro antagonism towards R. solanacearum, a wide spread, major bacterial pathogen of solanaceous crops. Isolate F.Pd19 was found most effective antagonist against R. solanacearum under in vitro condition with an inhibition zone of 4.03cm in diameter and may serve as promising bioagent, which need further in vivo investigation.
Keywords: Plant disease-Biological control; Pseudomonads; Ralstonia solanacearum